Independent and Distinct Associations of FABP4 and FABP5 With Metabolic Parameters in Type 2 Diabetes Mellitus - Furuhashi, Masato; Sakuma, Ichiro; Morimoto, Takeshi; Higashiura, Yukimura; Sakai, Akiko; Matsumoto, Megumi; Sakuma, Mio; Shimabukuro, Michio; Nomiyama, Takashi; Arasaki, Osamu; Node, Koichi; Ueda, Shinichiro (Frontiers in Endocrinology, 2020)
Objective: Among fatty acid-binding proteins (FABPs), secreted forms of FABP4 and FABP5, which are expressed in adipocytes and macrophages, act as bioactive molecules. We investigated concentrations of FABP4 and FABP5 in patients with type 2 diabetes mellitus. Methods: As a sub-analysis study of the Randomized Evaluation of Anagliptin versus Sitagliptin On low-density lipoproteiN cholesterol in diabetes (REASON) trial, 256 patients (male/female: 146/110, age: 68±10 years) with type 2 diabetes mellitus and dyslipidemia who were receiving statin therapy were recruited. Patients who had been treated with a thiazolidinedione were excluded. Results: Several drugs which may modulate FABP4 levels including statins, dipeptidyl peptidase-4 inhibitors and angiotensin II receptor blockers had been administered in 100%, 81% and 51% of the recruited patients, respectively. The level of FABP4, but not that of FABP5, was significantly higher in females than in males. Multivariate linear regression analysis demonstrated that waist circumference (β=0.21), estimated glomerular filtration rate (β=-0.31), triglycerides (β=0.16) and FABP5 (β=0.39) were independent predictors of FABP4 level after adjusting age and sex. On the other hand, FABP5 level was independently associated with levels of FABP4 (β=0.57) and high-density lipoprotein (HDL) cholesterol (β=-0.12). Conclusions: Concentrations of FABP4 and FABP5 are independent predictors of each other in patients with type 2 diabetes mellitus. There are distinct independent associations of FABP4 with renal dysfunction, adiposity and hypertriglyceridemia and there is a distinct independent association of FABP5 with a low HDL cholesterol level in type 2 diabetic patients with dyslipidemia at high risks for cardiovascular disease who are receiving statin therapy.